The Refugia Attract Arthropods in a Paddy Field in Malang, East Java, Indonesia - Amin Setyo Leksono; Jati Batoro; Anisa Zairina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
A study on the effect of refugia areas to attract on Arthropods has been done in a semi-organic paddy field in Malang, from March to June 2017. The arthropod was measured by abundance, diversity and composition variables. Arthropod observations were performed on 6 plots of 1 m2 each, consisting of 3 plots on the side near the Refugia area (treatment) and 3 plots on the opposite side (control). The refugia areas consisted of plants as follows chili (Capsicum frutescens), the wild cosmos (Cosmos caudatus), the long beans (Vigna unguiculata), and Marigold (Tagetes erecta). The visual encounter surveys method was conducted for 15 minutes on each plot. There were 2249 individuals of Arthropod observed visually in the study sites. This study showed that of the abundance (mean ± SE) of Arthropod visitors was lower in plots adjacent to refugia areas (treatment) (33.7± 2.63), than that far from Refugia area (control) (38.33 ± 2.54); while the taxa richness and diversity was higher found in treatment plots. The species richness in the treatment plots (12.2 ± 0.70) was higher than that in control (9.70 ± 0.51). The diversity of Arthropod visitors in the treatment plots (2.10 ± 0.07) was also higher than that in control (1.71 ± 0.07). Proportion of predator in the treatment plots was almost twice higher (33.14) that in the control plots (17.65); while that of herbivore was vice versa. This meant the refugia areas have attracted more predators. The composition of Arthropod visitors was remarkable affected by treatment. The abundance of common predator families such as Coccinellidae, Coenagrionidae and Oxyopidae were higher in treatment plots.